2012
DOI: 10.1038/ejhg.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

Ehlers–Danlos syndrome type VIII is clinically heterogeneous disorder associated primarily with periodontal disease, and variable connective tissue features

Abstract: We would like to dedicate this article to the memory of David Rimoin, MD, PhD, who passed away on May 27, 2012. He was an outstanding geneticist, mentor, and human being.Ehlers-Danlos syndrome (EDS) type VIII (periodontitis type) is a distinct form of EDS characterized by periodontal disease leading to precocious dental loss and a spectrum of joint and skin manifestations. EDS type VIII is transmitted in an autosomal dominant pattern; however, the mutated gene has not been identified. There are insufficient da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…Other inconstant features of EDS-VIII, such as a marfanoid habitus, a characteristic triangular facies, minimal skin hyperextensibility, and moderate joint hypermobility, were not present. The same periodontal disease in his mother reinforced the hypothesis of a hereditary disease, and other causes of autosomal dominant periodontitis were ruled out [3, 4]. Morphological abnormalities of collagen were observed in our patient's skin.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Other inconstant features of EDS-VIII, such as a marfanoid habitus, a characteristic triangular facies, minimal skin hyperextensibility, and moderate joint hypermobility, were not present. The same periodontal disease in his mother reinforced the hypothesis of a hereditary disease, and other causes of autosomal dominant periodontitis were ruled out [3, 4]. Morphological abnormalities of collagen were observed in our patient's skin.…”
Section: Discussionsupporting
confidence: 76%
“…Interpretation of these plaques as simple stasis dermatitis [10] does not fully account for their clinical characteristics. Indeed, as in our patient, their clinical features are the brownish color, the atrophic aspect, the well-circumscribed border, and the atypical topography on pretibial areas [24, 6]. Pathological examination of skin biopsies from these lesions revealed nonspecific dermal fibrosis and hemosiderin deposition [2].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…32 To date, this is the only confirmed X-linked form of EDS. Recently, Reinstein et al 33 have suggested that there is little molecular or clinical justification for considering EDS-PH as a separate entity from XL-PH, but instead they proposed that there is a spectrum of vascular and connective tissues anomalies associated with this condition for which all individuals with loss-offunction mutations in FLNA should be evaluated.…”
Section: Classificationmentioning
confidence: 99%
“…The skeletal phenotypes include joint laxity and dislocations, Marfanoid habitus, osteopenia, early-onset osteoarthritis, pectus deformity, scoliosis and pes planus. 33 …”
Section: Clinical Manifestationsmentioning
confidence: 99%